Wind power potential and usage in the coastal regions of Turkey - Ilkilic, Cumali; Aydin, Huseyin (Pergamon-Elsevier Science Ltd, 2015)
In this study, the potential of wind power in the coastal areas of Turkey have been studied. Current potential of the wind energy in coastal areas and its usage in Turkey have been investigated. The main purpose of this study is to investigate the wind energy plants in coastal regions of Black Sea, Marmara, Aegean and Mediterranean regions and project in Turkey. The wind energy potentials of all regions in Turkey have been investigated and utilization of the wind energy in coastal regions of Turkey was also studied. Various regions have been analyzed by taking wind data into account that had been measured in hourly time series in the windy locations. The coastal regions of Aegean, Marmara and East-Mediterranean have high wind energy potentials and wind densities. The wind data used in this study have been obtained taken from Electrical Power Resources Survey and Development Administration (EIEI) of Turkey. Istanbul, Izmir, Datca, Bandirma, Antalya, Canakkale and Hatay areas have been found to be the most promising areas for wind energy systems with their wind densities. Sinop, Gokceada, and Mersin follows these areas. It can be suggested the there are many suitable areas, for wind energy applications and investments, especially many of them are clustered in coastal regions in Turkey. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Wind energy; Renewable energy; Turkey